1993
DOI: 10.1121/1.405621
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile adaptation enhances amplitude discrimination

Abstract: Human psychophysical detection and amplitude discrimination thresholds for 25-Hz sinusoidal vibrations were measured on the thenar eminence using two-interval forced-choice tracking, in the unadapted state and following exposure to 25-Hz adapting stimuli representing a range of amplitudes (5-25 dB SL). As expected, detection threshold was elevated 6 to 7 dB for each 10-dB increase in the adapting stimulus. In contrast, amplitude difference thresholds for 10 and 20 dB SL standard stimuli were generally lowest w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 24 publications
(36 reference statements)
5
44
1
Order By: Relevance
“…The effects of delivering an adapting stimulus on the perception of subsequent test stimuliparticularly the reduction in sensation -has been characterized in some detail (Delemos and Hollins, 1996;Gescheider et al, 1995;Goble and Hollins, 1993;Laskin and Spencer, 1979;Tommerdahl et al, 2005a;Verrillo and Gescheider, 1977). Many psychophysical studies have reported that the presentation of an adapting stimulus causes an increase in the detection threshold, and thus a reduction in the perceived intensity, of a subsequent stimulus (for review see (Gescheider et al, 1995;Goble and Hollins, 1993;Verrillo, 1985;Verrillo and Gescheider, 1977)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of delivering an adapting stimulus on the perception of subsequent test stimuliparticularly the reduction in sensation -has been characterized in some detail (Delemos and Hollins, 1996;Gescheider et al, 1995;Goble and Hollins, 1993;Laskin and Spencer, 1979;Tommerdahl et al, 2005a;Verrillo and Gescheider, 1977). Many psychophysical studies have reported that the presentation of an adapting stimulus causes an increase in the detection threshold, and thus a reduction in the perceived intensity, of a subsequent stimulus (for review see (Gescheider et al, 1995;Goble and Hollins, 1993;Verrillo, 1985;Verrillo and Gescheider, 1977)).…”
Section: Discussionmentioning
confidence: 99%
“…Many psychophysical studies have reported that the presentation of an adapting stimulus causes an increase in the detection threshold, and thus a reduction in the perceived intensity, of a subsequent stimulus (for review see (Gescheider et al, 1995;Goble and Hollins, 1993;Verrillo, 1985;Verrillo and Gescheider, 1977)). More specifically, Gescheider et al showed that the threshold shift which occurred after the presentation of an adapting stimulus increased systematically with adapting stimulus duration (Gescheider et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two point discrimination (Vierck and Jones, 1970;Tannan et al, 2005a;Tannan et al, 2005b), measures of spatial acuity (Tannan et al, 2006;Tommerdahl et al, 2007), frequency discrimination (LaMotte and Mountcastle, 1975), temporal order judgment (Fiorio et al, 2003), and changes in responsivity with adaptation (Goble and Hollins, 1993;Tommerdahl et al, 2005c) are all examples of methods which could be easily implemented and/or modified with this device and could prove useful as sensory diagnostics in a number of clinical and/or clinical research settings. A number of features of this tactile stimulator system make it unique from previously reported devices, and these features will have a positive impact on its potential use in such non-laboratory settings.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of sinusoidal displacements to a single skin site via mechanical transducer has been used extensively for the study of flutter vibration in both psychophysical and neurophysiological settings for a number of decades (exemplary uses of such a device are described in (Mountcastle et al, 1969;Vierck and Jones, 1970;LaMotte and Mountcastle, 1975;Juliano et al, 1989;Goble and Hollins, 1993;Tommerdahl et al, 1993;Tommerdahl et al, 1998;Tommerdahl et al, 2002)). Typically, stimuli that can be delivered through mechanical transducers -vertical displacement stimulators such as the one originally described by Chubbuck (Chubbuck, 1966) -that are used for studies of somatosensation are very well equipped to deliver sinusoidal stimuli at a frequency range (1 -250 Hz) with amplitudes of sufficient size (between 0 and 1000 μm) to activate a broad range of mechanoreceptors.…”
Section: Introductionmentioning
confidence: 99%